From Civil Rights to Armalites - Dochartaigh, Niall Ó. author. aut Link
XVI, 332 p.
Keywords: From Civil Rights to Armalites traces and analyses the escalation of conflict in Northern Ireland from the first civil rights marches to the verge of full-scale civil war in 1972, focusing on the city of Derry. It explains how a peaceful civil rights campaign gave way to increasing violence, how the IRA became a major political force and how the British army became a major party to the conflict. It provides the essential context for understanding the events of Bloody Sunday and a new chapter brings significant new material to the public debate around the Bloody Sunday Inquiry.